Prevalence, incidence, and trends of epilepsy among children and adolescents in Africa: a systematic review and meta-analysis - Gebeyaw Biset; Nigusie Abebaw; Natnael Atnafu Gebeyehu; Natan Estifanos; Endalk Birrie; Kirubel Dagnaw Tegegne (BMC, 2024)
Abstract Background Epilepsy contributes to a significant disease burden in children and adolescents worldwide. The incidence of childhood epilepsy is threefold higher in low and middle income countries compared in high-income countries. Epilepsy is a serious neurological condition associated with stigma and discrimination, an impaired quality of life, and other mental health related problems. Objective This study is aimed to synthesize existing evidence and estimate the pooled prevalence and incidence of epilepsy in children and adolescents in Africa. Methods A comprehensive and systematic search of relevant databases was conducted. The quality of each study was assessed using the Newcastle-Ottawa Quality Assessment Scale adapted for meta-analysis. Two reviewers screened retrieved articles, conducted critical appraisals, and extracted the data. Heterogeneity between studies was assessed by visual inspection of forest plots and statistically using Cochran's Q statistics and the I2 test. Publication bias was checked by visual inspection of funnel plots as well as statistically using Egger's correlation and Begg's regression tests. Finally, the pooled prevalence and incidence of childhood epilepsy were computed with 95% confidence intervals. Result In this review and meta-analysis 42 studies with 56 findings were included to compute the pooled prevalence of childhood epilepsy. On the other hand, 6 studies were included to estimate the combined incidence. The pooled prevalence of cumulative epilepsy was 17.3 per 1000 children. Whereas the pooled prevalence of active and lifetime epilepsy was 6.8 and 18.6 per 1000 children respectively. The pooled incidence of childhood epilepsy was 2.5 per 1000 children. Conclusion Nearly 1 in 50 children are suffering from epilepsy in Africa. However, little attention has been paid to the prevention and treatment of childhood epilepsy. Mass epilepsy screening, scaling up treatment coverage, and designing strict treatment follow up and monitoring mechanisms are recommended.